Empowering Schools to Integrate Climate Change Education into Their Curriculum - M. Amin; Hanik Yuni Alfiyah; Febriarsita Eka Sasmita; She Fira Azka Arifin (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
The Education Quality Improvement Consortium in schools conducted mentoring in Malang Regency to enhance teachers’ and students’ awareness and understanding of integrating climate change content into the learning curriculum. The program aimed to strengthen participants’ capacity not only to comprehend climate issues but also to take responsible environmental action. Mentoring was implemented through a training-based approach covering planning, implementation, simulation, and evaluation. Activities included developing training modules, conducting module simulations, and administering post-training assessments. Results showed that participants successfully produced training modules, carried out simulations effectively, and achieved strong post-test scores. Participants’ understanding of climate change reached an average of 91%, indicating solid conceptual mastery. Additionally, participants demonstrated high skills in integrating climate-related content into their learning plans, with an average score of 96%. Overall, the mentoring program proved effective in enhancing both conceptual mastery and curriculum-integration skills related to climate change education.